Aplikasi Budidaya Ikan Dalam Ember Dengan Akuaponik Di Desa Gedung Harapan, Lampung Selatan - Maretta, Gres; Darmawan, Andy; Sinaga, Ayu Oshin Yap; Sari, Dian Anggria; Chusniasih, Dewi; Wahyuni, Kurnia; Sari, Rara Mulia; Hidayat, Thaariq; Novrianti, Rima Arini; Azmi, Sarah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M), Institut Teknologi Sumatera, Lampung, Indonesia., 2024)
As human population grows, the demand for food production will increase and consequently causing greater stress to resources such as land and water. Aquaponic is a technology integrating hydroponic and aquaculture to optimize nutrient cycling. The problem faced by the residents of Gedung Harapan Village is that the community still has not utilized the potential for optimal use of house yards for aquaculture and agriculture. We introduce aquaponics technology to realize independence in fulfilling family nutrition in the Gedung Harapan Village, South Lampung. This activity resulted in an increase in participants' understanding and experience of fish farming in buckets (budikdamber) with aquaponics. It was advisable to encourage more people to implemented budikdamber to fulfill family nutrition.